Behavior of Zr–1Nb alloy in coarse- and ultrafine-grain states under laser-induced shock wave loading (Fracture and Structural Integrity, 2023)
The work is devoted to the study of the Zr-1Nb alloy in coarse-grained and ultrafine-grained states under laser-induced shock-wave loading. This material is of interest due to the application for the manufacture of shells for fuel elements of nuclear reactors. The properties of this alloy in the ultrafine-grained state is attracted for the reliability improvement of fuel rods in wide range of load intensity. Shock wave loading was carried out using a Beamtech SGR-Extra-10 high-energy nanosecond laser. The free surface velocity profiles were registered by the VISAR system. Mechanical characteristics are obtained using velocity profiles. It is shown that the spall strength and dynamic elastic limit for the coarse-grained state are higher than for the ultrafine-grained state. In general, the Zr-1Nb alloy in the ultrafine-grained state is more susceptible to spall fracture, including laser shock peening. Numerical simulation of the process under study has been carried out using statistically based nonlinear model of solid with defects and finite element method to describe the deformation behavior and fracture of the material under shock-wave loading. Simulation results are qualitatively consistent with experiments in the prediction of the conditions of spall failure.
Keywords: Zr-1Nb alloy; shock-wave loading; ultrafine-grain state; structural studies; spall fracture